PERANCANGAN APLIKASI PENGAJUAN CUTI KARYAWAN PT. INDOMARCO ADI PRIMA MENGGUNAKAN PHP NATIVE - Noppy Hadisuwarno; R. Hudan Muchtadi; Sigit Auliana (INFOTECH journal, 2024)
The employee leave request application is a crucial need for large companies like PT. Indomarco Adi Prima to improve the efficiency of leave management. This study aims to design a web-based leave request application using PHP Native to simplify the process of submitting, approving, and tracking employee leave status. The system development method used is Waterfall, consisting of phases such as requirement analysis, design, implementation, and testing. The application is designed to be easily accessible in real-time, providing transparency and accuracy in leave management. Testing results show that the system can expedite the leave request process, minimize administrative errors, and enhance human resource management efficiency within the company.